Effect Of Difference In The Number Of Fruit Arrangements On The Level Of Mechanical Damage And Quality Of Strawberries (Fragaria Sp.) Cultivars Shed During The Storage Period - Aunillah, Ade; Romadhon, Choirul; budirokhman, dodi (Ann Publisher, 2025)
This study seeks to assess the impact of varying quantities of fruit arrangements in packaging on the extent of mechanical damage and the quality of strawberry (Fragaria sp.) cultivars during the storage duration. The study was conducted in the Product Processing Technology Laboratory, Faculty of Agriculture, Gunung Jati Independent University, Cirebon, from May 2024 to June 2024. The research employed an experimental procedure utilizing a Complete Random Design (RAL) with three treatment levels (1-layer fruit arrangement, 2-layer fruit arrangement, and 3-layer fruit arrangement), replicated nine times, resulting in 27 experimental units (27 packages). The observed factors were mechanical damage, weight loss, fruit hardness, total dissolved solids, and vitamin C content. The data were evaluated using the F test at a 5% significance level, and if a significant effect was observed, the Scott Knott test was subsequently applied at the same error level. The results indicated that the variation in the quantity of fruit arrays within the package influenced fruit weight loss, total dissolved solids, and vitamin C content in strawberries (Fragaria sp.). The optimal configuration of strawberries, considering mechanical damage, weight loss, fruit hardness, total dissolved solids, and vitamin C content, is a two-layer arrangement.